Emotional Expression of the Interjection 哎呀 Aiya - Rafidah Aulia; Hermina Sutami (Fakultas Sastra Universitas Darma Persada, 2022)
Interjection has no concrete meaning like noun, verb, nor adjective. It appears in spoken language to express one’s emotion in a certain condition or situation. The interjection 哎呀 aiya is one of the most frequently used interjection in modern Chinese. Concerning哎呀, Oxford Concise Chinese Dictionary (2010:1) only mentions that 哎呀is used to express surprise or discontent. We presume that there are more emotions available to be expressed. Based on the lack of types of emotions in the Chinese dictionary, the aim of this research is to examine kinds of emotions by analyzing the spoken language from a Chinese drama. The data is taken from dialogues containing 哎呀. This allows the researchers to observe the types of positive and negative emotions of 哎呀 in detail. This research uses Paolo Santangelo’s theory of emotion. He classifies emotions into 5 categories: (1) positive expectation and interaction, (2) satisfactory affects, (3) negative projection, (4) aggressive-opposing emotions, and (5) unsatisfactory affects. The method used to ascertain the type of emotions is done by considering the context where 哎呀appeared. From the context, it will determine the type of emotions. The result shows that the interjection 哎呀can express 5 types of emotions, such as hope, empathy, surprise, happiness, satisfy, worry, fear, angry, etc. The novelty of this research is to give types of emotions in detail.